2017
DOI: 10.14740/jem394w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficacy of Potassium Iodide Preparation for Radioactive Iodine Therapy in Graves’ Disease: A Retrospective Chart Review

Abstract: Background: Pretreatment by antithyroid drugs (ATDs) before radioactive iodine therapy (RAIT) for Graves' disease (GD) is often performed to avoid aggravation of thyroid function including thyroid storm. However, in patients suffering from adverse effects of ATDs, potassium iodide (KI) is often selected to treat hyperthyroidism before RAIT in Japan. The aim of this study was to evaluate the efficacy of KI preparation for RAIT in GD and whether a short-term discontinuation of KI before RAIT is a safe and useful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Regarding iodine restriction, it is common practice to follow a low-iodine diet (excluding seaweed and its processed products, with an inorganic iodine equivalent of 250-400 μg/day) for almost a week before results showed a significant difference in RAIU between the KI and MMI groups (29.9% vs. 62.9%; p = 0.002). However, Tachibana suggested that the 4 days of KI discontinuation before RIT may have contributed to the low RAIU in the KI group [10]. The present study aimed to investigate the effect of KI on RAIU before RIT in GD patients with appropriate iodine restriction.…”
mentioning
confidence: 91%
“…Regarding iodine restriction, it is common practice to follow a low-iodine diet (excluding seaweed and its processed products, with an inorganic iodine equivalent of 250-400 μg/day) for almost a week before results showed a significant difference in RAIU between the KI and MMI groups (29.9% vs. 62.9%; p = 0.002). However, Tachibana suggested that the 4 days of KI discontinuation before RIT may have contributed to the low RAIU in the KI group [10]. The present study aimed to investigate the effect of KI on RAIU before RIT in GD patients with appropriate iodine restriction.…”
mentioning
confidence: 91%